Low-dose combined oral contraception in women in pre- and perimenopausal period - Pertyński, Tomasz; Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2006)
Low-dose combined contraceptive tablet is an attractive form of contraception for menopausal women. A method of high contraceptive efficacy, it produces some extra-contraceptive effects, alleviating vasomotor symptoms, preventing osteoporosis, and reducing risks of ovarian and endometrial cancers. Naturally it also has some side-effects, but with low hormone dose administration and proper patient qualification they appear to be extremely rare.